A thermo-alkali stable and detergent compatible processive β-1,4-glucanase from Himalayan Bacillus sp. PCH94 - Thakur, Vikas; Singh, Dharam (Frontiers in Microbiology, 2022)
Present study reports a novel and robust GH9 processive endoglucanase β-1,4-glucanase from Bacillus sp. PCH94 (EGaseBL) with thermo-alkali stable properties. The EGaseBL gene was cloned in pET-28b(+) and expressed in Escherichia coli BL21(DE3) cells. The recombinant protein was purified 94-fold with a yield of 67.8%. The biochemical characterization revealed an active enzyme at a wide pH (4.0–10.0) and temperature (4–100°C). It showed a Km and Vmax of 1.10 mg/ml and 208.24 IU/mg, respectively, using β-glucan as a substrate. The EGaseBL showed dual activities for endoglucanase (134.17 IU/mg) and exoglucanase (28.76 IU/mg), assayed using substrates β-glucan and Avicel, respectively. The enzyme is highly stable in neutral and alkaline pH and showed a half-life of 11.29 h, and 8.31 h in pH 7.0 and 9.0, respectively. The enzyme is also compatible with commercial detergents (Tide, Surf, Ghadi, Raj, and Healing tree) of the Indian market and retained > 85% enzyme activity. Concisely, robustness, extreme functionality, and detergent compatibility endorse EGaseBL as a potential bioresource for the detergent industry, in addition to its implications for the bioethanol industry. Highlights – Cloning, expression, and purification of putative novel GH9 family β-1,4-glucanase. – Processive endoglucanase with CBM3 domain and bi-functional (endo/exo) activity. – Broad pH-temperature active and stable enzyme. – Compatible with commercial detergent powders.